A strain gage technique for the determination of mixed mode stress intensity factors of orthotropic materials. (15th January 2017) - Chakraborty, Debaleena; Chakraborty, D.; Murthy, K.S.R.K.
Abstract: A theoretical frame work is developed for strain gage based determination of mixed mode ( KI / KII ) stress intensity factors (SIFs) in slant edge cracked plate (SECP) made of orthotropic materials. Using three parameter strain series around the crack tip and appropriate stress functions, the present formulation shows that mixed mode SIFs in orthotropic materials could be determined using only four strain gages. A finite element based methodology is developed to determine the upper bound on the radial location ( r max ) of strain gages ensuring accurate determination of SIFs. Proposed technique is applied to numerical simulation of [02 /90]2S and [0/±45/90]S glass-epoxy SECP laminates to demonstrate accurate determination of mixed mode SIFs by placing the gages within r max . Results from the present work provide clear guidelines in terms of number of strain gages and their suggested locations for accurate determination of mixed mode SIFs in orthotropic materials.